STRUCTURAL ANALYSIS OF THE "GOOD NOTE, GOOD BALL FROM THE AVAILABILITY OF TECHNICAL AND FINANCIAL RESOURCES. (Fiep Bulletin - online, 2011)
This study aims to analyze the public policies of sport and leisure in the Viçosa city, Minas Gerais, based on the project "Good Note, Good for Ball," whose objective is to meet the needs of a portion of the underprivileged society. It was considered among other factors, the technical aspect, which aims to avaluate if teachers are meeting the children´s necessities, the most practiced and whether the used facilities and materials are in accordance with the requirements thereof. It was necessary to analyze the design basis, as well as the interference of the same, drawing on a methodology that prioritizes the analysis of questionnaires containing objective questions and discourse, and literature review, enabling the evaluation of the extent of it. Considering the longevity of the project and the results achieved so far, the inclusion of that meets the objectives, especially when determining the law number 8069 of July 13, 1990, which leads us to conclude that the goals are being achieved, even that the work still to be developed with some difficulty and insufficient incentives when it comes to financial resources.
Keywords: Sport; Recreation; Public Policy